NCOG-04. EFFECTS OF PROTON RADIATION ON BRAIN STRUCTURE AND FUNCTION IN LOW GRADE GLIOMA. (5th November 2018) - Parsons, Michael; Hoebel, Katharina; Chang, Ken; Pongpitakmetha, Thanakit; Beers, Andrew; Brown, James; Kalpathy-Cramer, Jayashree; Sherman, Janet; Shih, Helen; Dietrich, Jorg
Abstract: INTRODUCTION: Previous studies have shown progressive global brain volume loss over a 1–2 year period after treatment for glioblastoma with conventional chemoradiation. The pathogenesis of this toxicity is not well understood, though may reflect unintentional exposure of normal brain to photon irradiation. Proton, as compared to photon, irradiation reduces exposure to brain areas outside the target. To explore the possibility that proton radiation therapy limits neurotoxicity seen in our previous studies, we followed a cohort of patients treated with proton radiation over a 2-year period with serial imaging and neuropsychological evaluation, in whom we have previously reported stable cognitive function. METHODS: 20 patients with low grade glioma (13 male, mean age 37.5y) were treated with proton radiation (54Gy(RBE), 1.8Gy/fx). Volumetric MRI analysis was conducted at baseline and 2 years post-treatment (interval mean/SD=26.4/4 months) on 18 subjects using an automated deep learning algorithm to segment grey and white matter in the hemisphere opposite to brain tumor. Neuropsychological evaluations were conducted on 16/18 subjects at similar timepoints (interval mean/SD=25.7/3.2 mos; 2 subjects did not complete post-treatment evaluations). RESULTS: There was no significant change in grey (t=0.98; p=ns) or white matter t=-1.46; p=ns) volume over the 2-year post-treatment interval. Neuropsychological index scores were chosen to evaluate broad domains that might be sensitive to diffuse volume loss (IQ, processing speed, working memory, delayed recall). There were no significant changes in cognitive performance. Correlations between volumetric and cognitive change were nonsignificant across all domains. CONCLUSIONS: In contrast to our prior studies demonstrating neurotoxic effects on brain volume following standard chemotherapy in combination with photon irradiation, no similar effects were observed following proton irradiation. While tumor biology effects on neurotoxicity and methodological differences are considered, proton irradiation appears to preserve brain structure and function over a comparable 2-year period. HS and JD contributed equally.